Multimodal Discourse Analysis of TV Series HOMELAND: A Case of Pakistan - Munazar Aziz (Journal of Peace, Development and Communication, 2021)
This study is based on Multimodal discourse analysis of the popular American political drama series Homeland. It discusses the agenda-setting role of the American television industry and its relationship with the US government. The study is based on the premise that drama can be used as a key factor for a country's propaganda and foreign policy agendas. Using a qualitative approach, we aimed to investigate the portrayal of the Pakistani government and its security and secret agencies in Homeland. Because of the series’ long duration, this research is limited to the first four seasons only. The study results revealed that the Pakistani government, army, and security agencies, especially inter-services intelligence (ISI),were negatively portrayed. Among all the three categories, the role of ISI is depicted as the most negative. Keywords: Homeland, Multimodal discourse, Agenda setting, Pakistan, foreign policy